Two Novel Thermotolerant Methane Oxidizers from a Tropical Natural Gas Field in Bangladesh - Islam, Tajul; Hossain, Maqsud; Tabassum, Naushin; Haque, Mahir Amer; Reza, Hasan Mahmud; Øvreås, Lise (Bangladesh Journal of Microbiology, 2022)
Aerobic thermotolerant methane oxidizers utilize methane as a sole carbon and energy source, and predominantly they are associated with the phylum Proteobacteria. Here we present two further new strains (HGS-45: coccusshaped and HGF-47: rod-shaped and vibrioid) of thermotolerant obligate proteobacterial methanotrophic bacteria, which were isolated from an abandoned tropical natural gas field wet soil sample in the northeast of Bangladesh. Strains are Gram-negative, nonmotile, and capable of growth on methane and methanol as their energy sources. Isolates are thermotolerant and could grow up to 52oC, optimally at 42oC, but show no growth at 55 or 15oC. Based on 16S rRNA gene sequence analyses and phylogenetically, HGS-45 is most closely related to the obligate Type Ib methanotroph Methylococcus capsulatus of the family Methylococcaceae, whereas HGF-47 is affiliated to Type IIa methanotroph Methylocystis sp. of the family Methylocystaceae and possesses Type II intracytoplasmic membrane (ICM) systems. Genes of particulate methane monooxygenase (pMMO) and the methanol dehydrogenase (MDH) were detected by PCR. Southern-blot analyses of genomic DNA from both strains were positive, implying the aerobic biological oxidation process from methane to methanol by the pMMO. Each strain presumably represents a novel species. Furthermore, both strains will increase our knowledge of thermotolerant methanotrophic proteobacterial diversity, cohabitation, and their participation to global carbon cycles as well as signifying biological methane sinks in the terrestrial natural gas field ecosystems. Bangladesh J Microbiol, Volume 38, Number 2, December 2021, pp 63-71